The 18th International Conference on Experimental Mechanics 2018
DOI: 10.3390/icem18-05352
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of Additive Manufacturing Specimens: A Comparison with Casting Processes

Abstract: Abstract:In this paper, the specificity and/or the common features of materials coming from such new additive manufacturing processes will be compared to more classical one, like casting process. Fatigue properties of Ti-6Al-4V specimens built by EBM and SLM are first compared depending on several process parameters. Then, at the microstructure scale, it is shown that surface defects and unmelted zones seem to be the dominant features. It will be shown that similarities can then be drawn with casting processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…In Figure 13, the results from the present study are compared with the reported scatter bands for cast, cast plus hot isostatically pressed (HIP), and wrought/annealed processed Ti-6Al-4V [66]. Overall, the fatigue data obtained in this work is in the range of Ti-6Al-4V produced by casting and corroborates reasonably well with the properties reported in the open literature [15,57,59,[67][68][69], especially considering the broad scatter of the fatigue life data [70]. The current data also indicate a strong influence on fatigue life from both the surface finish and oxygen content, as evident by the IS Ti-6Al-4V material exhibiting the highest fatigue performance, with results that were in the range of parts that had been cast plus HIP.…”
Section: Fatigue Testingsupporting
confidence: 85%
“…In Figure 13, the results from the present study are compared with the reported scatter bands for cast, cast plus hot isostatically pressed (HIP), and wrought/annealed processed Ti-6Al-4V [66]. Overall, the fatigue data obtained in this work is in the range of Ti-6Al-4V produced by casting and corroborates reasonably well with the properties reported in the open literature [15,57,59,[67][68][69], especially considering the broad scatter of the fatigue life data [70]. The current data also indicate a strong influence on fatigue life from both the surface finish and oxygen content, as evident by the IS Ti-6Al-4V material exhibiting the highest fatigue performance, with results that were in the range of parts that had been cast plus HIP.…”
Section: Fatigue Testingsupporting
confidence: 85%
“…An estimation of the starting amplitude based on the tensile strength was refrained from due to pronounced scattering. 25,26 The test series for estimating fatigue strength was accomplished based on six samples, thus meeting the minimum required number of samples. 16 With respect to the corresponding equation according to the IABG method, an average fatigue strength of about 191 MPa is established for the as-built condition.…”
Section: Resultsmentioning
confidence: 99%
“…9. 167 In addition, the standard range for polished wrought and casting specimens is provided. X – Y and Z are the manufacturing directions of the specimens.…”
Section: B-based Approaches For Modification Of Bioresponse and Impro...mentioning
confidence: 99%